2007
DOI: 10.1175/mwr3382.1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Distribution Associated with Landfalling Tropical Cyclones over the Eastern United States

Abstract: Tropical cyclones (TCs) making landfall over the United States are examined by separating those associated with precipitation predominantly left of their tracks from those with the same to the right of their tracks. Composites of atmospheric variables for these two TC categories are performed and analyzed using potential vorticity (PV) and quasigeostrophic (QG) frameworks. Dynamical signatures are retrieved from these composites to help understand the evolution of precipitation in these storms. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
137
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 57 publications
16
137
0
Order By: Relevance
“…A comparison with totals greater than 150 mm contained in the NHC report [3] showed that the UPD tended to underestimate storm total rainfall by 50-75 mm, but the locations of the higher amounts were consistent. Underestimation of rainfall by this interpolated and gridded dataset is expected and has been documented for TCs by Atallah et al [6], yet these results suggest that the locations of the highest rainfall totals should be comparable across storms.…”
Section: Characteristics Of Track Trajectoriessupporting
confidence: 71%
See 3 more Smart Citations
“…A comparison with totals greater than 150 mm contained in the NHC report [3] showed that the UPD tended to underestimate storm total rainfall by 50-75 mm, but the locations of the higher amounts were consistent. Underestimation of rainfall by this interpolated and gridded dataset is expected and has been documented for TCs by Atallah et al [6], yet these results suggest that the locations of the highest rainfall totals should be comparable across storms.…”
Section: Characteristics Of Track Trajectoriessupporting
confidence: 71%
“…This limits the ability to investigate rainfall produced on the right side of the storm's track. Previous studies have used this dataset to examine rainfall from TCs [6,41], supporting its use in the current study. The fact that strong winds near the TC's center causes undercatch in rain gauges leading to lower rainfall totals should also be noted [42][43][44].…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…The bulk upscale influences of convection in baroclinic cyclones obviously force the downstream synoptic scale and instant mesoscale environment. This includes: enhanced differential cyclonic vorticity advection ahead of weak upstream troughs resulting from convection-generated enhanced downstream ridging and jet development with landfalling and recurving tropical cyclones [23] [24]; vorticity buildup and merger in vortical hot convective towers throughout initial tropical cyclogenesis [25]; and mesoscale ridging in the upper troposphere ahead of convection linked with mesoscale convective vortices [26].…”
Section: Introductionmentioning
confidence: 99%